A lightning strike to the head causing a visual cortex defect with simple and complex visual hallucinations. Issue 4 (16th March 2007) - Kleiter, Ingo; Luerding, Ralf; Diendorfer, Gerhard; Rek, Helga; Bogdahn, Ulrich; Schalke, Berthold
Abstract : The case of a 23-year-old mountaineer who was hit by a lightning strike to the occiput causing a large central visual field defect and bilateral tympanic membrane ruptures is described. Owing to extreme agitation, the patient was set to a drug-induced coma for 3 days. After extubation, she experienced simple and complex visual hallucinations for several days, but otherwise recovered largely. Neuropsychological tests revealed deficits in fast visual detection tasks and non-verbal learning, and indicated a right temporal lobe dysfunction, consistent with a right temporal focus on electroencephalography. Four months after the accident, she developed a psychological reaction consisting of nightmares with reappearance of the complex visual hallucinations and a depressive syndrome. Using the European Cooperation for Lightning Detection network, a meteorological system for lightning surveillance, the exact geographical location and nature of the lightning flash were retrospectively retraced.